2019
DOI: 10.1039/c9sm01394f
|View full text |Cite
|
Sign up to set email alerts
|

A colorimetric and fluorescent sensor for the detection of both fluoride ions and trifluoroacetic acid based on acylhydrazone derivatives

Abstract: An acylhydrazone-based colorimetric and fluorescent sensor (PAH-8) for the detection of F− and TFA/TEA has been studied. PAH-8 solution and organogel are highly selective and sensitive to F− among various tested anions in DMSO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The result was similar with those of uoride ion probes based on acylhydrazone skeleton reported previously. [40][41][42][43][44][45] To gain further insight into the observed difference of red shi value of the absorption band between SHJ-1 and SHJ-2 during the uoride ion sensing, the optimized geometries for probes and probes with F À were optimized by DFT calculation using Gaussian 16, respectively. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result was similar with those of uoride ion probes based on acylhydrazone skeleton reported previously. [40][41][42][43][44][45] To gain further insight into the observed difference of red shi value of the absorption band between SHJ-1 and SHJ-2 during the uoride ion sensing, the optimized geometries for probes and probes with F À were optimized by DFT calculation using Gaussian 16, respectively. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The result was similar with those of fluoride ion probes based on acylhydrazone skeleton reported previously. 40–45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Second, an acylhydrazone group was introduced into the molecule because studies have shown that acylhydrazone group can be protonated and used to detect acid or acid vapors. 32,35 Meanwhile, triphenylamine group as a strong electron donor group and acylhydrazone group with certain electron-accepting properties can form a donor−acceptor (D− A) structure, giving the molecule a certain solvatochromic effect. 36 In addition, the introduced aclhydrazone group and long alkyl chain have the ability to induce molecular selfassembly to form a gel according to prior experience.…”
Section: Introductionmentioning
confidence: 99%
“…There are many analytical tools like atomic absorption/emission/accelerator available and in usage by the researchers, lacks lower limits of certain cations and anions especially in the biological and environmental species. These techniques are moderately unpredictable, required expensive instrumentation, making them fallacious for onsite detection.…”
Section: Introductionmentioning
confidence: 99%